2004
DOI: 10.1016/j.ijid.2003.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Plasma fibronectin as a marker of sepsis

Abstract: Plasma FN appears to act as a marker of sepsis in that patients showed diminished pFN levels. Along with other clinical and laboratory variables, the use of this marker would allow a rapid diagnosis of sepsis and limit the number of blood cultures to be processed and the number of antibiotic prescriptions, particularly when symptoms are insidious and diagnosis is doubtful. We propose further and more complex studies using a higher number of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…The importance of fibronectin in sepsis remains unclear, and very few results have been published so far. According to previous research, the concentration of plasma FN was significantly reduced in patients with sepsis compared to values measured in healthy volunteers [17], and pFN was indicated as an early sepsis marker. Additionally, lower plasma FN levels were observed in cases of fungal sepsis than in cases of bacterial sepsis [18].…”
Section: Introductionmentioning
confidence: 81%
“…The importance of fibronectin in sepsis remains unclear, and very few results have been published so far. According to previous research, the concentration of plasma FN was significantly reduced in patients with sepsis compared to values measured in healthy volunteers [17], and pFN was indicated as an early sepsis marker. Additionally, lower plasma FN levels were observed in cases of fungal sepsis than in cases of bacterial sepsis [18].…”
Section: Introductionmentioning
confidence: 81%
“…FN has multiple functional domains that can bind to integrin, collagen, fibrin and heparin, and participate in cell adhesion, migration, proliferation and differentiation ( Hynes, 2012 ; Mao & Schwarzbauer, 2005 ; Pankov, 2002 ). More and more studies have demonstrated that FN plays an important role in assessement the severity of severe infection and sepsis ( Lemańska-Perek & Adamik, 2019 ; Ruiz Martin et al, 2004 ).…”
Section: Introductionmentioning
confidence: 99%
“…A large release of TNF-α has been shown to be associated with harmful pathophysiological effects and increased mortality from septic shock [42]. In addition, the abnormally diminished concentration of plasma Fn has been used as a biomarker in evaluating sepsis [15]. The reduction in the plasma Fn concentration observed in patients with sepsis may arise from intravascular coagulation and cryofibrinogenemia, which is likely due to increased plasma Fn catabolism secondary to the intravascular formation of fibrin [15].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the abnormally diminished concentration of plasma Fn has been used as a biomarker in evaluating sepsis [15]. The reduction in the plasma Fn concentration observed in patients with sepsis may arise from intravascular coagulation and cryofibrinogenemia, which is likely due to increased plasma Fn catabolism secondary to the intravascular formation of fibrin [15]. However, the mechanisms underlying this reduction remain unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation